THE IMPACT OF IMPLEMENTING GOOGLE SITES AS AN INTERACTIVE MULTIMEDIA LEARNING MEDIA ON INCREASING STUDENT LEARNING ACHIEVEMENT - Alexander Mahombar (Jurnal Pembelajaran Sains, 2024)
The aim of this research is to examine the impact of implementing Google Sites as an interactive multimedia learning medium on increasing student learning achievement. Interactive multimedia learning media using Google Sites provides students with the opportunity to access study material again at home. The type of research that researchers use is quasi-experimental with only one experimental class. This research is quantitative research with an instrument for measuring learning achievement in the form of 10 multiple choice questions. The results of the research state that there is an important impact from the application of Google Sites as an interactive multimedia learning medium on student learning achievement in vibration and wave material with a significance value of 0.90 which exceeds the limit value of 0.05. The average pre-test score obtained was 45.87, while the average post-test score was 87.45. The percentage increase in student learning achievement through the application of Google Sites as an interactive multimedia learning media was 91% or it could be said that the use of Google Sites as an interactive multimedia learning media was effective on increasing student learning achievement.